COMPARISON OF BEHAVIOR BETWEEN ISLAMIC AND COMPOSITE INDEX IN INDONESIA AND MALAYSIA - Stevani Adinda Nurul Huda (Universitas Gunadarma, 2017)
This study aims to analyze whether there is difference of behavior between Islamic index (Jakarta Islamic Index (JII) and Kuala Lumpur Shariah Index (KLSI)) as well as conventional index (Jakarta Composite Index (JCI) and Kuala Lumpur Composite Index (KLCI)) in Indonesia and Malaysia. This study use Vector Auto regression (VAR) or Vector Correction Model (VECM) to respectively as certain if co integration exists. Based on the results, it shows that there is no difference of behavior between Islamic index and conventional index in Indonesia and Malaysia. It suggested that both countries make some changes in the Islamic index structure to differentiate from the conventional. For the investors should pay more attention to the inflation rate rather than the other macro economic variables, because inflation rate consistently determine these indexes. Keywords: Investment, Sharia capital market, conventional capital market, macroeconomy